2008
DOI: 10.3727/000000008783907116
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neutrophil Gelatinase-Associated Lipocalin as a Predictor of Organ Recovery from Delayed Graft Function after Kidney Transplantation from Donors after Cardiac Death

Abstract: Because of a worldwide shortage of renal grafts, kidneys procured from donors after cardiac death (DCD) have recently become an important source of renal transplants. However, DCD kidneys often have complications with delayed graft function (DGF) and recipients require hemodialysis (HD) in the early period after kidney transplantation (KTx). This study evaluated serum NGAL as a potential specific parameter to predict early functional recovery of transplanted DCD kidneys. The average serum neutrophil gelatinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 25 publications
(3 reference statements)
3
40
0
Order By: Relevance
“…In the transplant setting, a small clinical study showed that the intensity of NGAL staining in renal biopsies 1 h after reperfusion correlated well with the cold ischemic time and requirement for dialysis [22]. Urinary levels of NGAL on the day of transplant have also been shown to significantly predict DGF [23] and graft recovery [24]. However, NGAL has not been previously investigated in the pig in this setting.…”
Section: Discussionmentioning
confidence: 96%
“…In the transplant setting, a small clinical study showed that the intensity of NGAL staining in renal biopsies 1 h after reperfusion correlated well with the cold ischemic time and requirement for dialysis [22]. Urinary levels of NGAL on the day of transplant have also been shown to significantly predict DGF [23] and graft recovery [24]. However, NGAL has not been previously investigated in the pig in this setting.…”
Section: Discussionmentioning
confidence: 96%
“…NGAL staining in early biopsies from patients receiving a cadaveric kidney was strongly correlated with peak postoperative serum creatinine, which occurred days later. In a recent study, Kusaka et al [88] suggested that monitoring of serum NGAL levels might allow for the prediction of graft recovery and the need for hemodialysis after a kidney transplantation from a donor after cardiac death. They observed a dramatic fall in serum NGAL on the first postoperative day after transplantation from a living related donor reaching normal range on the 10th postoperative day.…”
Section: Kidney Transplantation: Delayed Graft Functionmentioning
confidence: 99%
“…They observed a dramatic fall in serum NGAL on the first postoperative day after transplantation from a living related donor reaching normal range on the 10th postoperative day. All of the patients after cadaveric kidney transplantation (kidney procured after cardiac death) required hemodialysis for 5-22 days [88] . In the study of Schaub et al [89] the stable transplant with the subclinical tubulitis group had slightly higher levels of NGAL (p = 0.06) than the stable transplant with the normal tubular histology group with a substantial overlap.…”
Section: Kidney Transplantation: Delayed Graft Functionmentioning
confidence: 99%
“…Therefore, many efforts have been made to identify novel biomarkers that could accurately and sensitively reveal early renal damage after transplantation. Recently, additional molecules, including gelatinaseassociated lipocalin (8,9), kidney injury molecule 1 (10), and interleukin 18 have been investigated to discriminate renal lesions after transplant and to evaluate the prognosis and efficacy of the therapeutic regimen (11).…”
mentioning
confidence: 99%